Aprendizagem de Programação de Computadores por meio da metodologia Peer Instruction em ambiente blended learning - MESSAGE, Carla Plantier (2019)
The present research is linked to the research line Training and Action of the Teaching Profession and Educational Practices of the Postgraduate Program in Education of the University of Western São Paulo, in São Paulo State, Brazil. The purpose of this study was to understand the implications of the learning process involving the Peer Instruction active methodology in a blended learning environment in the Computer Programming face-to-face course of a Bachelor´s Program in Electrical Engineering. The blended learning approach is a mix of teaching and learning practices and methodologies in classroom and online environments. In this perspective, the active methodology Peer Instruction was applied, supported by digital technologies of information and communication. This methodology aims to encourage peer instruction so that students form groups to exchange information about curricular contents, through which one helps the other in the collaborative construction of knowledge. Therefore, the student advances from mere spectator of the traditional classes to an active participant of his/her learning. The theoretical framework of this study is based on the following researchers: Mazur, Sousa, Vygotsky, Moran, Moore and Tori. In methodological terms, this study is an intervention research of strategic action. The participants of the research were 11 students of the Bachelor´s Program in Electrical Engineering and the researcher, who is also the professor of the course. Data collection took place through questionnaires and observations. The data collection took place during 5 interventions in the semester through 3 questionnaires and observations. At the beginning of the intervention, the questionnaires were applied socio-cultural and socioeconomic Profile and Learning Styles, during all 5 interventions, notes of the observations were made by the researcher and in the last intervention was applied the questionnaire on the Conceptions about the application of Peer Instruction methodology in a blended environment learning. Data analysis was performed from the creation of categories that were defined based on the literature and data collected. The analysis of the results confirmed that the methodology developed in the Computer Programming course was well evaluated by the students due to the dynamism, autonomy and collaborative learning. The researcher found that the way she proceeded with the course developed in students the habit of prior study, collaborative work and learning became significant.